The survey effectiveness of parental education on the basis of Acceptance and Commitment Therapy (ACT) on parental monitoring in the parents of the high school girl students in Isfahan city - Zohreh Kermani Alghoreyshi; Mohammad Reza Abedi; Marzieyh Malekiha (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study was survey the effectiveness of parental education on the basis of Acceptance and Commitment Therapy (ACT) on parental monitoring in the parents of the high school girl students in Isfahan city. The research method was a quasi-experimental research, a pre-test, post-test design with a control group and follow up. The research population was all of parents of high-school girl’s students at 2019 year that from this population, 30 members were selected with available sampling and were randomly divided to an experimental and control group (each group with 15member). In experimental group, for 10 session (each session 90 minute), parental education sessions on base of Acceptance & Commitment Therapy (ACT) has been done as independent variable, but control group received any intervention. For data gathering, were used from parental monitoring questionnaire- researcher made. Data was analyzed with SPSS-23 and calculating decryption indicators and Anova with repeated measure. The results indicated meaningful difference between scores means of parental monitoring and its subscales between experimental and control group thus on this basis can be concluded that parental education sessions on the basis of Acceptance and Commitment Therapy (ACT) has been effect on parental monitoring (p<0.001) and it’s subscales (awareness, p<0.001; communication, p < 0.005; supervision, p< 0.001, concern, p < 0.005 and acceptance, p< 0.001).